A European research agenda for lifelong learning. (4th April 2011) - Sloep, Peter; Boon, Jo; Cornu, Bernard; Klebl, Michael; Lefrère, Paul; Naeve, Ambjörn; Scott, Peter; Tinoca, Luis
It is a generally accepted truth that without a proper educational system no country will prosper, nor will its inhabitants. With the arrival of the post-industrial society, in Europe and elsewhere, it has become increasingly clear that people should continue learning over their entire lifespans lest they or their society suffer the dire consequences. But what does this future lifelong learning society exactly look like? And how then should education prepare for it? What should people learn and how should they do so? How can we afford to pay for all this, what are the socio-economic constraints of the move towards a lifelong-learning society? And, of course, what role can and should the educational establishment of schools and universities play? This are questions that demand serious research efforts, which is what this paper argues for.